THE EXISTENCE OF WAQF IN ESTABLISHING A SUSTAINABLE COMMUNAL SPACE - Agus Rochani; Nany Yuliastuti; Budi Sudarwanto (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
In Indonesia, the number of urban settlements continues to grow, while the paucity of communal space in urban areas persists. Therefore, it is vital to support local potential to achieve long-term success. Waqf generosity is one form of social development that has been institutionalized in society. Waqf, or benevolent generosity in surrendering personal possessions for the public good, is practiced by almost the entire Muslim community worshiping Allah SWT. This research aims to uncover the role of waqf in the formation of public spaces from a long-term viewpoint. This study employs a case study method to comprehend the real life of the waqf spatial entity in the urban village. The research location is Tugurejo Village, Tugu District, Semarang City. The study deviates from the grand theory to investigate the events at the study site. Interviews, observation, and secondary data are used to acquire data; descriptive methods are used to analyze the data, and the research findings are fed back into the grand theory. The research found that sustaining communal ownership rights and productivity advantages between generations ensures the sustainability of waqf as a communal space, resulting in a sustainable community structure.